Design Of Heart Rate Monitoring Tools And Applications Based On Mobile Systems - Sulaiman; Achmad Fauzi; Siswan Syahputra (International Journal of Health Engineering and Technology, 2022)
The heart is one of the important organs owned by humans that functions to pump blood throughout the body and accommodate it again after cleaning the lungs. Heart rate beats per minute (bpm) is a parameter to indicate the condition of the heart, and the way to know the condition of the heart is to know the frequency of the heart rate. This heart rate monitoring tool is designed based on the NodeMCU ESP8266 and pulse sensor to detect heart rate. This study aims to make it easier to find out the heart rate in real time. The NodeMCU ESP8266-based heart rate monitoring tool has been designed with a pulse sensor to detect heart rate. The heart rate data from the monitoring tool will then be sent via a wifi network connection and displayed on the Smartphone.